رواية "دم لفطير صهيون" لنجيب الكيلاني : دراسة تحليلية وفنية - Tholhah Damid Abdul Muiz (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This study addresses the concept of Islamic literature and its content by Najib Al-Kilani, and the extent to which the content addressed in his novel “Blood for The Matzo of Zion” corresponds to this concept. The study aims to evaluate the extent of the success of the writer Najib Al-Kilani in implementing his concept of Islamic literature in the theme of the novel, and interest in studying the artistic structure that Al-Kilani employs in it according to modern anecdotal rules. The study contributes towards the study of Najib Al-Kilani's concept of Islamic literature and its content, and its application in his literary work. The researcher first collected information related to the writer's views on Islamic literature, and analyzed it, then studied his point of view regarding the content that must be addressed within the literary work. The study discovers that the content of Islamic literature is life in its entirety, so the Islamic writer must adhere to this content, and adherence to the content means not opposing the fundamentals and principles of religion, and treating them according to Islamic perception. The researcher discovers that Al-Kilani succeeded in applying his concept of Islamic literature in his novel “Blood for The Matzo of Zion”; he adhered to its content, and dealt with its issues according to Islamic perception, except in his portrayal of the protagonist represented in the beloved cleric of Christ, he also succeeded in employing the artistic structure of the novel, as the elements of its structure came in mastery and precision. The study concludes that Al-Kilani's novel is an Islamic one who is committed to content and art.